Table of Content - -, (Journal of Educational and Psychological Sciences, 2024)
Table of Content:1. The effectiveness of the seven – cycle learning strategy 7E’s on the achievement and attitude towards the course for students of the Curriculum and Teaching Methods course at Shaqra University in the Kingdom of Saudi ArabiaCo- Prof. Lafa Mohmmed H. Alotaibi2. Requirements for activating the digital economy in the education sector in Oman to face challenges and crises – the case of Covid-19 pandemicMr. Salman Sloum Khamis Alhinai, Co-Prof. Omer Ismail Hamad, Co-Prof. Khalaf Marhoun AlAbri , Prof. Ali Sharaf Al Musawi3. The Effectiveness of a Training Program Based on the Universal Design for Learning in Improving the Teaching Competencies of Teachers of Students with Learning Difficulties in Al-Ahsa GovernorateMrs. Wijdan Rashid Al-Rasheed, Dr. Tareq Yousef Melhem4. Employing some Web 2.0 applications in developing the skills of producing digital stories  for kindergarten teachersMrs. Shoq Hasan Al-Sa'ida5. The Level of Psychological Adjustment Among a Sample of Female Breast Cancer Patients  in Riyadh Province and Its Relationship to Self-EsteemMrs. Eman Mohammad Sharee Al-Otibi6. Psychometric characteristics for attachment styles among a sample of secondary school students in Buraidah cityMrs. Nafla Sulaiman Al-Qusayer, Prof. Sufyan Ibrahim Al-Rebdi
Keywords: Journal of Educational and Psychological Sciences